Treatment of atopic dermatitis with upadacitinib: adcare single center experience - Fomina, Daria S.; Mukhina, Olga A.; Mikhailova, Valeria I.; Lebedkina, Marina S.; Sedova, Elizaveta L.; Bobrikova, Elena N.; Elisyutina, Olga G.; Fedenko, Elena S.; Nurpeisov, Tair T.; Karaulov, Alexander V.; Lysenko, Mar’yana A.; Ensina, Luis Felipe C. (Frontiers in Medicine, 2024)
Introduction: The role of upadacitinib in the management of moderate to severe atopic dermatitis seems promising, but more data on its efficacy and safety are needed. This study endeavors to assess the practical impact and safety of upadacitinib in patients with moderate to severe atopic dermatitis. The study aims to evaluate the efficacy and safety of upadacitinib in the treatment of moderate to severe atopic dermatitis, focusing on analyzing patient responses to the treatment. Methods: In this study, adult patients diagnosed with moderate to severe atopic dermatitis received upadacitinib at daily doses of 15 mg or 30 mg, as prescribed by their attending physicians. The therapeutic efficacy of upadacitinib was meticulously assessed using established clinical metrics. Simultaneously, a comprehensive safety assessment was conducted through monthly monitoring, including the evaluation of potential effects of upadacitinib intake on hepatic function, lipid profile, and hematopoiesis using the pertinent laboratory tests. Results: Sixteen participants were enrolled in the study. At 1 month follow-up, there was a significant reduction in the mean Eczema Area and Severity Index (EASI) score to 18.8 points , which further increased to 24 points at the 4-month mark. Additionally, 9 participants (56%) demonstrated an EASI-50 response after 1 month of treatment, with this response increasing to 9 participants (90%) after 4 months. Furthermore, enhanced therapeutic responses were observed at 4 months, with 6 patients (38%) achieving an EASI-75 response at 1 month and 8 patients (80%) achieving this milestone at the 4-month follow-up. This study highlights the potential of upadacitinib as an effective treatment option for moderate to severe atopic dermatitis. While it demonstrates improved symptom management, close monitoring for potential adverse events, particularly infections and the known risks of Janus kinase inhibitors, is essential. Further research is essential to determine the long-term safety and efficacy of upadacitinib.